Effects of tannase-converted green tea extract on skeletal muscle development - Ki-Bae Hong; Hee-Seok Lee; Jeong Sup Hong; Dong Hyeon Kim; Joo Myung Moon; Yooheon Park (BMC, 2020)
Abstract Background The aim of this study was to investigate the effect of tannase-converted green tea extract with a high (−)-epicatechin (EC), (−)-epigallocatechin (EGC), and gallic acid (GA) content on myotube density and fusion in normal and oxidative stress-induced C2C12 skeletal muscle cells. Although the use of green tea extract is considered beneficial, cellular and molecular mechanisms of action of tannase-converted green tea extracts that are used as potential muscle growth materials have not been thoroughly studied. Methods This study used histological analysis and molecular biology techniques, and compared the results with those for AMPK activator 5-aminoimidazole-4-carboxamide-1-β-D-ribonucleoside (AICAR) and green tea extracts. Results The myotube density of normal and oxidative stress-induced C2C12 cells was significantly higher in the tannase-converted green tea extract-treated group than that observed in the other groups (normal cells: P < 0.01; oxidative stress-induced cells: P < 0.05). In addition, tannase-converted green tea extract and green tea extract treatments significantly upregulated the genetic expression of myogenin, Myf5, and MyoD (P < 0.05). The levels of AMP-activated protein kinase-α (AMPKα) and muscle RING-finger protein-1 (MuRF-1) in the tannase-converted green tea extract group were higher than those in the AICAR and green tea extract groups (P < 0.05). Conclusions Taken together, our findings describe that the high levels of EC, EGC, and GA in the tannase-converted green tea extract are attributable to the morphological changes in C2C12 cells and intercellular signaling pathways. Therefore, tannase-converted green tea extract can be used in the treatment of sarcopenia.